Resource use Efficiency in Cultivation of Major Crops in Malappuram District - M.R., Dr. Indu. (Academy of Agriculture Journal, 2017)
Efficiency is an important concept in production economics when resources are constraint and opportunities of adopting better technologies are competitive. The efficiency in the use of various resources affects the productivity of crops, their costs and return structure and profit. Agricultural productivity depends on resource use efficiency of cultivated crops. Productivity of crops in Kerala shows wide fluctuations in past decades. The studies dealing with resource useÂ efficiency in Kerala agriculture is sporadic